Neutrophil chemotaxis and adhesion in preterm babies. Issue 7 (July 1992) - Carr, R; Pumford, D; Davies, J M
Abstract : To investigate the increased susceptibility to infection of very immature preterm neonates, neutrophil chemotaxis, Mac-1 adhesion receptor expression, and adherence to human umbilical vein endothelial cell monolayers (HUVE) were examined in neonates born at less than or equal to 32 weeks' gestation. Chemotaxis of neutrophils from well preterm neonates towards casein or zymosan activated serum (ZAS) was reduced (mean SE) being for casein 88.6 (3.8) microns; ZAS 76.2 (4.3) microns compared with adults (casein 117.8 (1.4) microns; ZAS 112.1 (1.4) microns), but similar to term neonate neutrophils (casein 92.7 (4.5) microns; ZAS 75.9 (3.1) microns). Stimulated Mac-1 expression showed a similar pattern: reduced on preterm neutrophils compared with adults, but similar to term neonates. Preterm and term neonate neutrophils were both hyperadherent to HUVE when unstimulated, but showed an equally impaired ability to increase adhesion following stimulation. Casein stimulated chemotaxis and stimulated Mac-1 expression 'matured' towards adult levels of performance four weeks after preterm birth. The increased incidence of sepsis in immature preterm infants is not due to greater defects of neutrophil migration.